Can Citizen Reporting System Be Effectively Constructed? A Study of Smart City Implementation in Indonesia - Andi Rahmat Hidayat (Magister Ilmu Administrasi Publik, 2021)
This study focused on Citizen Reporting System (CRS), which is one of the main pillars crucial in designing and implementing smart cities. The study had several objectives including determining the extent of public knowledge on the use of CRS, which was proposed in four leading applications of Makassar smart city programmes; Smart RT / RW application, Call Centre 112, Home care and Qlue; and identified factors that support and inhibit the development of citizen reporting system to develop recommendations for improvement of CRS, which will in turn have a positive impact on the implementation of smart city programmes in Makassar and Indonesia in general. The study used a sequential mixed method, specifically sequential explanatory strategies. The phases entailed conducting a survey to collect and analyse quantitative data; followed by conducting in-depth interviews to explore specific issues and obtaining in-depth information. The results showed that people’s knowledge and information about the smarty city programmes is still very low, a problem that hampers the use of these services by the community. Besides, another finding was that that the frequency of accessing internet and social media, and the will to actively participate in helping the government and reporting problems or issues in their neighbourhood by people in Makassar is sufficiently high. Thus, based on study results, the local government has an important asset it can use to develop a citizen reporting system, which is one of the key factors in the successful implementation of smart city programmes.